Biomechanical Comparison of the Holding Strength of a PEEK Locking Dorsal Plate Versus Lag Screw Fixation for Triple Arthrodesis. Issue 1 (19th August 2016) - Sabatini, Jefferson; Smith, Kenneth S.; Eberhardt, Alan; Kirchner, John S.
Category: Hindfoot Introduction/Purpose: Hindfoot arthrodesis is often the treatment of choice for hindfoot pain due to arthritis or advanced deformity. Good results are dependent on secure fixation while avoiding hardware related side effects. A small radiolucent locking dorsal circular plate placed into the talonavicular and calcaneocuboid joints may provide a low-profile solution for secure fixation of these joints. The goal of this study is to compare the fixation strength of a locking dorsal circular plate to that of the current gold standard technique of screw fixation. Methods: Eight matched fresh-frozen cadaveric foot-ankle pairs were obtained for comparison of the two fixation methods. One side of each matched pair was plated with a locking dorsal circular plate and the contralateral foot was fixed with partially threaded 4.5 mm cannulated screws. All subtalar joints were fixed with two 7.3 mm cannulated screws. Translational forces through a mechanical testing system (MTS) were applied to the constructs cyclically for 40 cycles followed by loading to failure. Displacement was recorded using two high-speed infrared cameras, following sets of orthogonal marker systems attached to each bone. Results: Cyclical loading trials found there to be no significant difference in resistance to motion between the two methods. However, specimens instrumented with plates had an approximately 400% higher load to failure (513.3 N vs 127.7 N) than specimens instrumented with screws. Conclusion: Locking dorsal circular plates are a viable option that provide equivalent and possibly better fixation strength than screw fixation for the talonavicular and calcaneocuboid components of a triple arthrodesis of the hindfoot. These plates are radiolucent allowing easy assessment of the fusion site. In addition, these plates have the theoretical benefit of being low profile to decrease tendon irritation and wound healing problems.